Attack on Titan. 31 - Isayama, Hajime, 1986- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2020)
A parade of massive Titans are roused from their centuries-long slumber, breaking free of the Walls to answer their founder's call, and only Eren knows where their march leads.